2021
DOI: 10.1190/int-2021-0012.1
|View full text |Cite
|
Sign up to set email alerts
|

Airborne and ground geophysical evaluation of potential mineralized zone in parts of Ilesha schist belt, southwestern Nigeria

Abstract: Integrated airborne and ground geophysical studies were conducted in parts of Ilesha schist belt, southwestern Nigeria. The goal was to provide a useful guide for mineral prospecting, with the hope of considerably narrowing down the future search for mineral deposits within the study area. Aeromagnetic and aeroradiometric data were analyzed for the reconnaissance study. In addition, the reduction-to-equator transform, analytic signal, tilt derivative, and Euler deconvolution filters were applied to the aeromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…8 38'77.64. Geologically, the area has been described by many researchers [16][17][18][19][20][21]. Their reports showed that the complex consist of the Schist belt, Porphyritic older granites Migmatite gneiss complex and Miscellaneous rock types.…”
Section: Study Areamentioning
confidence: 99%
“…8 38'77.64. Geologically, the area has been described by many researchers [16][17][18][19][20][21]. Their reports showed that the complex consist of the Schist belt, Porphyritic older granites Migmatite gneiss complex and Miscellaneous rock types.…”
Section: Study Areamentioning
confidence: 99%